2020
DOI: 10.1007/s12350-018-1388-3
|View full text |Cite
|
Sign up to set email alerts
|

SPECT myocardial perfusion imaging in liver transplantation candidates

Abstract: Abnormal SPECT MPI results in candidates for liver transplantation are infrequent compared to non-liver transplant patients and the incidence of obstructive CAD on subsequent angiography even less. Repeat testing in those on the transplant waiting list after initial normal test results appears to be of limited value. Stress-first protocols may be considered for the majority of these patients to reduce testing time and radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Currently, there is no consensus regarding cardiovascular testing in pre-LT patients, which is likely due to the heterogeneity of the published data and how CAD is defined. Contrary to the perfusion data presented by Duvall et al, 5 small studies of anatomical imaging have reported a higher prevalence of CAD. In a study of 85 low-CAD-risk patients with ESLD, Kemmer et al reported a prevalence of prognostically significant coronary artery calcium score (CAC) of [ 400 to be present in 19 (22%) with a prevalence of obstructive CAD on ICA to be 26%.…”
Section: Among Pre-lt Patients Without Known Cad Butcontrasting
confidence: 83%
See 1 more Smart Citation
“…Currently, there is no consensus regarding cardiovascular testing in pre-LT patients, which is likely due to the heterogeneity of the published data and how CAD is defined. Contrary to the perfusion data presented by Duvall et al, 5 small studies of anatomical imaging have reported a higher prevalence of CAD. In a study of 85 low-CAD-risk patients with ESLD, Kemmer et al reported a prevalence of prognostically significant coronary artery calcium score (CAC) of [ 400 to be present in 19 (22%) with a prevalence of obstructive CAD on ICA to be 26%.…”
Section: Among Pre-lt Patients Without Known Cad Butcontrasting
confidence: 83%
“…In this issue of the Journal, Duvall et al summarized their 10-year experience of cardiovascular risk stratification using SPECT MPI, in patients awaiting LT. 5 The authors evaluated clinical and SPECT MPI data from 34,551 patients who underwent stress MPI between 2004 and 2014. Of these, 2500 patients were evaluated pre-LT.…”
Section: See Related Article Pp 254-265mentioning
confidence: 99%
“…Nonetheless, a trend towards higher rates of peri-operative ischemic complications was noted in patients with a positive SPECT study. These findings were also confirmed in another study by Duvall et al [35].…”
Section: Myocardial Perfusion Imaging (Mpi)supporting
confidence: 83%
“…This high rate of normal perfusion studies is similar to a recent large cohort (n = 2500) of SPECT MPI studies performed for OLT cardiac risk evaluation. (24) The concern with this modality for assessing cardiovascular risk in ESLD is 2-fold: fig. 5.…”
Section: Discussionmentioning
confidence: 99%